A model to explain the impact of government revenue on the quality of governance and the SDGs - Stephen G. Hall; Bernadette O'Hare (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2022)
This paper empirically investigates the link between the level of government revenue per capita and six indicators of quality of governance in an unbalanced panel data set consisting of all countries in the world (217) using data from 1980 to 2020. It uses single-equation GMM techniques and a VAR and VECM approach to investigate this link. The results show a strong effect over time whereby an increase in government revenue leads to a steady improvement in governance. These findings suggest an important virtuous circle between government revenue and governance, indicating that additional government revenue can significantly impact the Sustainable Development Goals more than our previous work has suggested.
Keywords: I10; C01; C13; C20; 330; corruption; GMM; ECM; SDGs